KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IV PADA MODEL KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA ENGKLEK MATEMATIKA - Elsa Noviyanti; Sastra Wijaya; Fauzi Fadliansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of learning mathematics is not just to achieve student learning outcomes, but rather to achieve basic mathematical skills, namely communication. Based on the results of an interview with the class teacher with the initials